2021
DOI: 10.3390/cancers13061236
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Reverses Epithelial-Mesenchymal Transition Through Modulation of the TGF-β/Smad Signaling Pathway in Endometrial Cancer

Abstract: Endometrial cancer is a common gynecological cancer with a poor prognosis, mostly attributed to tumor metastasis. Epithelial–mesenchymal transition (EMT) can be mediated via transforming growth factor beta (TGF-β) signaling pathway, facilitating the ability of cancer cell invasion and migration. Isoliquiritigenin (ISL) is a flavonoid derived from licorice with reported antineoplastic activities. This study aims to investigate the anti-metastatic potential of ISL on endometrial cancer both in vitro and in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…EMT is one of the classical modes of tumourigenic invasion and metastases. 17 , 27 Many studies 29 , 30 have shown that Smad2/3 plays a central role in TGF-β-induced EMT. At the amino acid level, the most important difference between Smad2 and Smad3 is that the MH1 region of Smad2 has 2 more amino acid fragments than Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is one of the classical modes of tumourigenic invasion and metastases. 17 , 27 Many studies 29 , 30 have shown that Smad2/3 plays a central role in TGF-β-induced EMT. At the amino acid level, the most important difference between Smad2 and Smad3 is that the MH1 region of Smad2 has 2 more amino acid fragments than Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the expression of key transcription factors also acts as the driving force for EMT, such as TWIST1, TWIST2, ZEB1, ZEB2, SNAI1 and SNAI2 [ 16 , 17 ]. The critical role of EMT in the metastasis of various tumors has been clearly demonstrated by previous studies, including ovarian tumor [ 18 ], Endometrial Cancer [ 19 ] and nasopharyngeal carcinoma [ 20 ]. However, the upstream regulators for the EMT in CRC remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, endometrial cancer is the most common gynecologic cancer, with an increasing incidence worldwide. Patients that are diagnosed at an early stage present good prognosis and high survival rates, although when diagnosed at a late stage they have poor prognosis, mostly caused by tumor metastasis, which has low survival rates and limited treatment options [6][7][8][9]. Thus, improved treatment options for women that already present cervical and endometrial cancer are still necessary.…”
Section: Introductionmentioning
confidence: 99%